Ideational Meanings of Teachers' Utterances in Reading and Writing Classes - Sri Mulatsih; Mursid Saleh; Warsono Warsono; Issy Yuliasri (International Journal of Language Teaching and Education, 2018)
This study is aimed at describing the ideational meanings of teachers’ utterances in Reading and Writing classes. It reveals what processes, participants and circumstances are found in the teachers’ utterances. The data were taken from the Reading and Writing classes conducted at a university in Semarang city. The data were collected by video recording the teaching and learning processes in Reading and Writing classes, then they were analyzed by segmenting the utterances into clauses; identifying the process, participants, and circumstances; classifying the processes, participants and circumstances based on their type; and interpreting the data. The results showed that the processes mostly found in the teachers’ utterances in Reading class are relational ones with carrier and attribute as participants, the second are mental processes with senser and phenomenon as the participants, while in those of Writing class are material with actor and goal as participants and the second are relational with carrier and attribute as participants. Relational processes are dominant in Reading class because the teacher explained many terms or vocabularies found in the text to make the students really understand them. That material processes are dominant in Writing class is caused by the fact that in Writing class the teacher often asks the students to do some actions like writing or doing something.